2022
DOI: 10.1007/s11357-022-00587-3
|View full text |Cite
|
Sign up to set email alerts
|

Circulating interleukin-37 declines with aging in healthy humans: relations to healthspan indicators and IL37 gene SNPs

Abstract: Aging is characterized by declines in physiological function that increase risk of age-associated diseases and limit healthspan, mediated in part by chronic low-grade inflammation. Interleukin (IL)-37 suppresses inflammation in pathophysiological states but has not been studied in the context of aging in otherwise healthy humans. Thus, we investigated associations between IL-37 and markers of healthspan in 271 young (18–39 years; n = 41), middle-aged (40–64 years; n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…Based on the available data, it was not possible to define a reliable refence range for IL-38 in healthy volunteers, as was possible for the IL-37 data extracted from literature ( 13 ). This is remarkable as IL-37 has several isoforms that will probably not be determined by all ELISA kits ( 50 , 51 ). However, to give an estimation of a potential direction of a reference range of IL-38 we could rely on the data generated after exclusion of outliers.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the available data, it was not possible to define a reliable refence range for IL-38 in healthy volunteers, as was possible for the IL-37 data extracted from literature ( 13 ). This is remarkable as IL-37 has several isoforms that will probably not be determined by all ELISA kits ( 50 , 51 ). However, to give an estimation of a potential direction of a reference range of IL-38 we could rely on the data generated after exclusion of outliers.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the concept of inflammaging which was adopted by Ferrucci recognizes that the chronic low-grade inflammation milieu observed in older adults contributes to cardiovascular risk [ 133 ], and seems to play a role in the development of multiple age-related diseases and conditions, including frailty [ 134 ]. However, the pathways linking inflammaging to physiological function and healthspan in humans are not well-known [ 135 ].…”
Section: Aging-related Changes In Skeletal Muscle and Cardiovascular ...mentioning
confidence: 99%
“…Notably, a negative direction of associations of pre-frailty/frailty with IL-37, which was stably maintained across the regression models, is suggestive of the suppressive effect of pre-frailty/frailty on circulating levels of IL-37. Some clarifications come from the recent study, where it was found that plasma levels of IL-37 are lower in healthy elderly individuals than in middle-aged and young ones, despite elevations in proinflammatory markers [ 63 ]. These results suggest that IL-37 responsiveness to proinflammatory stimuli declines with age.…”
Section: Discussionmentioning
confidence: 99%